2017
DOI: 10.1107/s2053229617004429
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of photoactive manganese–carbonyl complexes derived from 2-(pyridin-2-yl)-1,3-benzothiazole and 2-(quinolin-2-yl)-1,3-benzothiazole

Abstract: PhotoCORMs (photo-active CO-releasing molecules) have emerged as a class of CO donors where the CO release process can be triggered upon illumination with light of appropriate wavelength. We have recently reported an Mn-based photoCORM, namely [MnBr(pbt)(CO)] [pbt is 2-(pyridin-2-yl)-1,3-benzothiazole], where the CO release event can be tracked within cellular milieu by virtue of the emergence of strong blue fluorescence. In pursuit of developing more such trackable photoCORMs, we report herein the syntheses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Transition metal complexes that can photochemically release carbon monoxide upon exposure to visible light have been reported recently (Chakraborty et al, 2014;Stenger-Smith et al, 2017). Facile release of carbon monoxide has been observed in manganese carbonyls containing acenaphthalene derivatives (Carrington et al, 2015) including the ligand MIAN {2-[(4-chlorophenyl)imino]acenapthylen-1-one}, the subject of this study, shown in the Scheme.…”
Section: Chemical Contextmentioning
confidence: 90%
“…Transition metal complexes that can photochemically release carbon monoxide upon exposure to visible light have been reported recently (Chakraborty et al, 2014;Stenger-Smith et al, 2017). Facile release of carbon monoxide has been observed in manganese carbonyls containing acenaphthalene derivatives (Carrington et al, 2015) including the ligand MIAN {2-[(4-chlorophenyl)imino]acenapthylen-1-one}, the subject of this study, shown in the Scheme.…”
Section: Chemical Contextmentioning
confidence: 90%
“…All reagents were of commercial grade and were used without further purification unless stated otherwise. 2-(Pyridin-2-yl)-1,3-benzothiazole (pbt) (Chen et al, 2001) and 2-(quinolin-2yl)-1,3-benzothiazole (qbt) (Stenger-Smith et al, 2017) were synthesized following reported procedures. 1,10-Phenanthroline (phen) was purchased from Sigma-Aldrich Inc. and was used as received.…”
Section: Methodsmentioning
confidence: 99%
“…This may be achieved by external stimuli such as enzymes, solvent, H 2 O 2 , , and light . The release of CO with the help of light is known as photoactivated CORMs (photo-CORMs), ,,− phot-CORMs has the advantage of controlled CO release. However, the general problem with most of the reported photo-CORMs is site specificity and predictable formation of a metal–coligand fragment, which might possess the biological activity of its own.…”
Section: Introductionmentioning
confidence: 99%